Structural features of the focal adhesion kinase–paxillin complex give insight into the dynamics of focal adhesion assembly - Bertolucci, Craig M. (Cold Spring Harbor Laboratory Press, 2005)
The C-terminal region of focal adhesion kinase (FAK) consists of a right-turn, elongated, four-helix bundle termed the focal adhesion targeting (FAT) domain. The structure of this domain is maintained by hydrophobic interactions, and this domain is also the proposed binding site for the focal adhesion protein paxillin. Paxillin contains five well-conserved LD motifs, which have been implicated in the binding of many focal adhesion proteins. In this study we determined that LD4 binds specifically to only a single site between the H2 and H3 helices of the FAT domain and that the C-terminal end of LD4 is oriented toward the H2-H3 loop. Comparisons of chemical-shift perturbations in NMR spectra of the FAT domain in complex with the binding region of paxillin and the FAT domain bound to both the LD2 and LD4 motifs allowed us to construct a model of FAK–paxillin binding and suggest a possible mechanism of focal adhesion disassembly.